многощЕтинковыЕ ЧЕРВИ ХРЕБТА РЕЙКЪЯНЕС (СЕВЕРНАЯ АТЛАНТИКА) [Polychaetous worms from the Reykjanes Ridge (the North Atlantic). Bottom Fauna from Mid-Ocean Rises in the North Atlantic. Donnayafauna Otkryto. Okeanicheskikh. Podnyatij. Severnaya. Atlantika] - Detinova, N. N. (Trudy Instituta okeanologii im. P.P. Shirshova, 1985)
During the 2th cruise of the R/V "Academic Mstislav Keldysh" at Rejkjanes Ridge (North Atlantic) there were found about 100 species of polychaetous annelids at the depths from 1330 to 2951 meters. Illustrated descriptions of 6 new species are given (Robertianella platychaeta sp.n., Branchamphiome islandica sp. п . , Euphrosine keldyshi sp.n., Aponuphis chistikovi sp.n .,. Oligobregma lonchochaeta sp.n:, melinna collare sp .n.). Euphrosinella gen .n. is described. The geographical distribution of the species is discussed. The polychaete fauna of this region seems to. consist of three main groups of specles: wide distributed eurybathic species, wide distributed abyssal species and north atlantic deep-water species.
World Polychaeta Database (WPolyD)